INOVASI PELAYANAN PRIMA PASPOR ONLINE DI KOTA MALANG - Ira Kustiani; Willy Tri Hardianto; Roro Merry Chornelia Wulandari (REFORMASI, 2021)
Abstract: Excellent service really needs to be owned and displayed when doing a job in a frontliner or customer service position and in excellent service it can be said to be good if it has served the community well. The purpose of this study is to find out about the success of using online passport services, find out the actors involved in online passport services in Malang City and describe the obstacles in implementing online passport services in Malang City. The research method used is qualitative research with in-depth data collection techniques, observation and documentation. Meanwhile, the data analysis used is purposive sampling. The result shows that the implementation of online passport service at the Immigration Agency Class 1 TPI Malang has been running since August 2017. The implementation of online passport service innovation cannot be separated from service innovations that can be said to be effective and efficient because it consists of several factors that influence the success of implementing these innovations. Factors that influence the implementation of innovation service include the character of the innovation (maker), the communication channel and the social system.Keywords: online passport; innovation; excellent serviceAbstrak: Pelayanan Prima sangat perlu untuk dimiliki dan ditampilkan pada saat melakukan suatu pekerjaan dalam posisi frontliner atau customer service dan dalam pelayanan prima dapat dikatakan baik apabila sudah melayani masyarakat dengan baik. Tujuan penelitian ini adalah untuk mengetahui tentang kesuksesan pengunaan pelayanan paspor online, untuk mengetahui aktor-aktor yang terlibat pelayanan paspor online di Kota Malang serta mendeskripsikan kendala dalam pelaksanaan pelayanan paspor online di Kota Malang. Metode penelitian yang digunakan adalah penelitian kualitatif dengan teknik pengumpulan data wawancara mendalam, observasi dan dokumentasi. Sementara analisis data yang digunakan adalah purposive sampling. Hasil penelitian menunjukkan bahwa penyelengaraan pelayanan paspor online di Instansi Imigrasi Kelas 1 TPI Malang sudah berjalan mulai berjalan bulan agustus 2017. Penyelengaraan inovasi pelayanan paspor online tidak lepas dari inovasi pelayanan yang sudah bisa dikatakan efektif dan efisien karena terdiri dari beberapa faktor yang mempengaruhi kesuksesan penyelengaraan inovasi tersebut. Faktor yang mempengaruhi kesuksesan penyelenggaraan pelayanan inovasi tersebut antara lain adalah faktor karakter inovasi (pembuat), faktor saluran komunikasi dan faktor sistem sosial.Kata Kunci: paspor online; inovasi; pelayanan prima